2004
DOI: 10.1103/physrevd.69.127301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electrodynamics and the acceleration of the Universe

Abstract: It is shown that the addition of a non-linear term to the Lagrangian of the electromagnetic field yields a fluid with an asymptotically super-negative equation of state, causing an accelerated expansion of the universe. Some general properties of nonlinear electromagnetism in cosmology are also discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
265
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(269 citation statements)
references
References 26 publications
(8 reference statements)
3
265
0
1
Order By: Relevance
“…(Clearly, this term should dramatically affect, for instance, the photon-B field interaction in intergalactic space, which is relevant to understand the solution to the Pioneer anomaly using NLED.). The consistency of this theory with observations, including the recovery of the well-stablished Coulomb law, was shown in [21] using the cosmic microwave radiation bound, and also after discussing the anomaly in the dynamics of Pioneer 10 spacecraft [22]. Both analysis provide small enough values for the coupling constant γ.…”
Section: Novello-pérez Bergliaffa-salim Nledmentioning
confidence: 90%
See 2 more Smart Citations
“…(Clearly, this term should dramatically affect, for instance, the photon-B field interaction in intergalactic space, which is relevant to understand the solution to the Pioneer anomaly using NLED.). The consistency of this theory with observations, including the recovery of the well-stablished Coulomb law, was shown in [21] using the cosmic microwave radiation bound, and also after discussing the anomaly in the dynamics of Pioneer 10 spacecraft [22]. Both analysis provide small enough values for the coupling constant γ.…”
Section: Novello-pérez Bergliaffa-salim Nledmentioning
confidence: 90%
“…Physical motivations for bringing in this theory have been provided in [21]. Besides of those arguments, an equally unavoidable motivation comes from the introduction in the 1920's of both the Heisenberg-Euler and Born-Infeld nonlinear electrodynamics discussed above, which are valid in the regime of extremely high magnetic field strengths, i.e.…”
Section: Novello-pérez Bergliaffa-salim Nledmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimdahl et al have suggested that a (timelike) vector force could be responsible for the present acceleration of the universe [27]. Also, it has been noted that the addition of higher-order powers of the Maxwell field-strength to the Lagrangian of an electromagnetic field might cause the universe to accelerate [28]. The literature on magnetic fields in the early universe is more extensive, see [29] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the triad evolution can be For integer values of n and fine-tuned initial conditions it is also possible to obtain histories where the equation of state w A remains constant at a value significantly smaller than −1 for a long period of time, and just recently approaches −1. For these models dw A /dz tends to violate the limit in (28). Certain analyses of supernova data [14] suggest that the equation of state has evolved from w DE ≈ 0 at z ≈ 1 to w DE < −1 today [14].…”
Section: Two Examplesmentioning
confidence: 99%